Theatre Reviews - Buckley, Thea; Walkling, Saffron (Multicultural Shakespeare: Translation, Appropriation and Performance, 2014)
The Taming of the Shrew, Globe to Globe. Dir. Haissam Hussain, 26-27 May 2012 Coriolanus, Edinburgh International Festival. Dir. Lin Zhaohua, 20-21 August 2013